(untitled) (El-Wahat Journal for Research and Studies, 2025)
This study aims to reveal the relationship between Jeffrey Young’s maladaptive early cognitive schemas and post-traumatic stress disorder among Firefighter. To verify the hypotheses, we relied on the descriptive approach (correlational studies), through which we applied both Jeffrey Young’s (EMS) scale and the maladaptive early cognitive schemas scale by Jeffrey Young. Post-traumatic stress disorder (CIDI) on a sample of 30 Firefighter. As for the correlation value of the total score of early maladaptive schemas and post-traumatic stress disorder, it was estimated at 0.35, which is a positive, average, and statistically significant value at the significance level of 0.05. Therefore, the hypothesis was fulfilled. Keywords: civil protection, Post-traumatic, stress, schemas. (EMS).